Kredibiliti Komunikator Berasaskan Manhaj Rabbaniyyah - Muhammad Taufik Md Sharipp; S. Salahudin Suyurno; Abdul Rauf Ridzuan; Muaz Hj. Mohd Noor (USIM Press, 2024)
Vol. 32 (2020): ULUM ISLAMIYYAH The Malaysian Journal of Islamic Sciences [December 2020]